Anthropologisch-philosophische Bedingungen der sozialen Kommunikation. Anthropologic-philosophical conditions of social communication - Andrzejewski, Bolesław (Glottodidactica, 2016)
In the article one adopt the assume that the communication has the social dimension and is related to human being. One can define it only after the definition of human being. The question: what communication do one need? is closely connected with the results of anthropologic- philosophical researches. The homo-theories of today are much one-sided, first of all they alien the man from his natural and social environment (for instance the symbolism). We propose the definition of man plaited in the environment and we call him homo universus. Helpful is here the romantic and neoromantic philosophy, especially its theory of language and communication.